2018
DOI: 10.1002/anzf.1324
|View full text |Cite
|
Sign up to set email alerts
|

Creating Community – The Introduction of Multi‐Family Therapy for Eating Disorders in Australia

Abstract: It is well established that connection and support are associated with supporting recovery from eating disorders whereas isolation and feeling misunderstood can be barriers to change. While the consumer and recovery movements have long advocated for treatments that go beyond symptom reduction alone to include factors such as connection with others, there are few treatments that are designed to target these directly for young people with eating disorders and their families. In 2014 the Sydney Children's Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
(77 reference statements)
2
11
0
Order By: Relevance
“…They found in it a space within which they could share, and have recognised, the difficulties within their family with others who understood because they had similar difficulties. This created a powerful feeling of ‘being on the same wavelength’ and a fellowship and solidarity both liberating and painful [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They found in it a space within which they could share, and have recognised, the difficulties within their family with others who understood because they had similar difficulties. This created a powerful feeling of ‘being on the same wavelength’ and a fellowship and solidarity both liberating and painful [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dawson and colleagues [ 28 ] found that MFT fosters social and personal resources by creating community , and that the core principles of MFT include creating solidarity . Tantillo and colleagues` [ 22 ] study showed that parents in MFT found it refreshing to be with others who really understood, experiencing it as being like coming home.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eating disorders are the result of a complex interaction of constitutional, biological, social, and psychological factors. Research on eating disorders focuses on the role of mental disorders (Chami et al, 2020;Dawson et al, 2018;Palavras et al, 2020;Weiss et al, 2019) and sociocultural factors (Ordaz et al, 2018;Rodgers et al, 2018;2019Yamamiya et al, 2016). Currently, there are more and more studies that examine various types of mental self-regulation among the significant factors of nutritional behavior (Annesi et al, 2016;Dohle et al, 2018;Eschenbeck et al, 2016;Kennel, 2018;Menzie et al, 2017).…”
Section: Problem Statementmentioning
confidence: 99%